Anti-Hyperlipidemia Effects of Sijukkot Leaf Extract Ethanol (Lactuca Indica) - Ida Duma Riris; Saronom S ilaban; Marini Damanik; Nora Susanti (Indian Journal of Forensic Medicine & Toxicology, 2022)
Lactuca indica from Indonesia (Humbang Hasundutan) is a plant used to treat as antihyperlipidemia :Cholesterol, Trigliserida (TG), High Density Lippoprotein (HDL), Low Density Lippoprotein (LDL),on 28 male rats of the wistar strain (Rattus norvegicus) that have been given high-fat diets were given to3 control groups, namely rats given standard feed, groups of rats given standard and high-fat diets, andgroups of rats given simvastatin with treatment for 21 days. The groups with different doses were 100mg/kg bw, 200 mg/kg bw, 300 mg/kg bw and 400 mg/kg bw. Giving the ethanol extract of the leaves ofthe sijukkot plant has an effect on reducing total cholesterol levels. With the analysis obtained that theShapiro-Wilk Normality Test with a sig value > 0.05, the data is normally distributed. The results of theanalysis in the Test of Homogeneity of Variances table obtained a Sig value of 0.510. Cholesterol SigValue 0.510 > 0.05; TG 0.102>0.05; HDL 0.01 <0.05 and LDL 0.257> 0.05. Thus, the ethanolic extractof sijukkot leaves gave a positive effect on cholesterol levels in the serum lipid profile of High DensityLippoprotein (HDL and Low Density Lippoprotein (LDL).